Hubungan antara Pengetahuan dan Sikap dengan Tindakan Penggunaan Alat Pelindung Diri pada Pekerja Mebel di Desa Leilem Dua Kecamatan Sonder Kabupaten Minahasa - Mongkau, Febrial R. P.; Rattu, Joy A. M.; Suoth, Lery F. (Universitas Sam Ratulangi, 2020)
Abstract: Furniture worker is one of the jobs that is at risk of working accidents and illness related to work. Therefore, it is necessary to control work hazard, one of them is by using personal protective equipment (PPE). During observation, many workers had lack of understanding about the importance of using PPE. This study was aimed to obtain the relationship between knowledge and attitude and the action of using PPE among furniture workers at Leilem, Sonder. This was a quantitative study with a cross sectional design. The instruments in this study were questionnaires and chek-list sheets. We used the chi-square test with a p-value of 0.05 to analyze the relationships. The results showed that of 68 respondents, 67 had good level of knowledge about the PPE, while 1 respondent had low level of know-ledge. There were 36 respondents that had good attitude about using PPE meanwhile those with poor attitude were 32 respondents. Respondents that did not use complete PPE were 18 worker while those who did not use PPE were 50 worker. The chi-square test showed a p-value of 1.00 for the relatjonship between knowledge and the action of using PPE and a p-value of 0.418 for the relationship between attitude and the action of using PPE. In conclusion, there were no relationships between knowledge and the action of using PPE as well as between attitude and the action of using PPE among the furniture workers at Leilem, Sonder.Keywords: knowledge, attitude, action of using personal protective equipmentÂ Abstrak: Pekerja mebel merupakan salah satu pekerjaan yang berisiko kecelakan kerja dan penyakit akibat kerja. Untuk itu perlu adanya pengendalian bahaya salah satunya dengan menggunakan alat pelindung diri (APD). Dari hasil pengamatan banyak pekerja yang kurang memahami pentingnya penggunaan APD saat melaksanakan pekerjaan. Penelitian ini bvertujuan untuk mengetahui hubungan antara pengetahuan dan sikap dengan tindakan penggunaan APD pada pekerja mebel di Desa Leilem Dua Kecamatan Sonder Kabupaten Minahasa. Jenis penelitian ialah kuantitatif dengan desain potong lintang. Instrumen penelitian ini menggunakan kuesioner dan lembar chek-list. Analisis hubungan menggunakan uji chi-square (p=0,05). Hasil penelitian mendapatkan 68 responden penelitian. Responden dengan tingkat pengetahuan baik tentang APD sebanyak 67 orang, sedangkan yang pengetahuan kurang baik berjumlah 1 orang. Responden dengan sikap baik terhadap penggunaan APD ialah 36 orang dan yang sikap tidak baik 32 orang. Responden yang menggunakan APD tidak lengkap 18 orang dan yang tidak menggunakan APD 50 orang. Hasil uji chi-square hubungan pengetahuan dengan tindakan penggunaan APD mendapatkan nilai p=1,00 dan hubungan sikap dengan tindakan penggunaan APD mendapatkan nilai p=0,418. Simpulan penelitian ini ialah tidak terdapat hubungan antara pengetahuan dan sikap dengan tindakan penggunaan APD pada pekerja mebel di Desa Leilem Dua, Sonder.Kata kunci: pengetahuan, sikap, tindakan penggunaan alat pelindung diri